Dynamics of denitrification performance and denitrifying community under high-dose acute oxytetracycline exposure and various biorecovery strategies in polycaprolactone-supported solid-phase denitrification. (1st February 2021) - Yu, Hui; Ye, Xin; Feng, Lijuan; Yang, Jingyi; Lan, Zeyu; Ren, Chengzhe; Zhu, Wenzhuo; Yang, Guangfeng; Zhou, Jiaheng
Abstract: Solid-phase denitrification (SPD) is a promising technology for nitrate-rich water purification. This study aimed to examine the variation in denitrification performance and denitrifying community under high-dose acute oxytetracycline (OTC) exposure and various biorecovery strategies. The denitrification performance was impaired significantly after one-day OTC shock at 50 mg L −1 in a continuous-flow SPD system supported by a polycaprolactone (PCL) carrier but could rapidly recover without the addition of OTC. When 50 mg L −1 OTC stress was applied for a longer time in the batch tests, a natural recovery period of more than 20 days was required to reach more than 95% nitrate reduction. Under the same conditions, the addition of both mature biofilm-attached PCL carrier and fresh biofilm-free PCL carrier significantly shortened the recovery time for efficient nitrate reduction, mainly due to the increase in organic availability from the PCL carriers. However, the composition of the microbial community notably changed due to the effects of OTC according to high-throughput sequencing and metagenomic analysis. Genes encoding NAR and NIR were much more sensitive than those encoding NOR and NOS to OTC shock. Tetracycline resistance gene (TRG) enrichment was 15.86% higher in the biofilm that experienced short-term OTC shock than in the control biofilm in the continuous-flow SPD system. Highlights: Continuous-flow SPD system rapidly recovered after one-day OTC shock at 50 mg L −1 Microbial and denitrifiers community could not recover correspondingly. Denitrification genes related with NAR and NIR much more sensitive to OTC shock. Tetracycline resistance genes increased by 15.86% higher after multi-shock OTC. Mature-biofilm attached and fresh biofilm-free PCL addition both favoured recovery.